Chronic Kidney Disease: A Case Series (Part 6) (Advancements in Homeopathic Research, 2024)
In their previous five publications Gupta et. al. demonstrated that patients of chronic kidney  disease (CKD) and acute renal failure (ARF) can be  successfully managed by homoeopathic medicines.  This sixth case series put forth herewith is on successful  management of CKD patients by maintaining their  serum creatinine level and eGFR within a reasonable  range, delaying further deterioration and improving  their quality of life for a considerable period of time  without haemodialysis. The first case in this series  is of 63-year old normotensive, non-diabetic female  suffering from CKD having single kidney after  donating a kidney to her son having CKD. Her S.  Creatinine level is maintained for more than 5 years  and she is still under treatment. The second case is  of a 63-year old hypertensive, nondiabetic female.  Her S. creatinine and eGFR was maintained for more  than 3 years. In third female patient aged 75-year,  who was hypertensive and non-diabetic, S. creatinine  and eGFR was maintained for about 3 years.
Keywords: Haemodialysis (HD); peritoneal dialysis (PD); chronic kidney disease (CKD); chronic renal failure (CRF); end stage renal disease (ESRD); serum urea; blood urea nitrogen (BUN); serum creatinine; estimated glomerular filtration rate (eGFR); renal transplant; homoeopathic treatment